Re-investigation and line identifications for W11+ in the visible range. (16th February 2022) - Fu, N; Lu, Q; Yan, C L; Xu, G Q; Wang, K; Chen, C Y; Zou, Y; Xiao, J
Abstract: We present a new investigation of unidentified emission lines in 350–660 nm from W 11+ at a compact electron-beam ion trap in Shanghai. To help the line identification, transition energies of the lowest 48 levels are calculated by the large-scale relativistic configuration interaction and multiconfiguration Dirac–Hartree–Fock calculation. The results from the two calculations are in good agreement with each other and the deviation is 0.66% on average. By using the collisional-radiative model implemented in the flexible atomic code, six observed lines for the visible spectrum of W 11+ are identified as magnetic-dipole transitions from 4 f 12 5 s 2 5 p 3 and 4 f 13 5 s 2 5 p 2 configurations.